PENINGKATAN KAPASITAS PETANI DALAM PENERAPAN BIOPESTISIDA PENGENDALI HAMA PADA TANAMAN PADI SAWAH (Oryza sativa L.) DI DESA CIASMARA KECAMATAN PAMIJAHAN - Gema Lentra Putri Aghis; Rudi Hartono; Ait Maryani (Sekolah Tinggi Pariwisata Mataram, 2020)
Pest attacks in the agricultural sector have become commonplace in every planting season and even pest attacks can reduce rice productivity 2-4 tons / ha, new farmers apply pest control according to the recommendations of around 38-40% less than 50% of the extension agent's target so the importance of using biopesticides as an effort to reduce pest attacks through the application of Pest Control Biopesticides which aim to Describe the increase in farmer capacity in the application of Pest Control Biopesticides, Analyze Factors related to increasing the capacity of farmers in the application of Pest Control Biopesticides in rice plants. The study was conducted in Ciasmara Village, Pamijahan District. The sample of the research is active farmers who are 40 members of farmer groups, using Descriptive Data Analysis, Spearman Rank Analysis. The results of research on improving the capacity of farmers in the application of biopesticides at the Knowledge stage are starting to recognize the existence of innovations and gain some understanding of the innovations functioning, followed by the stages of persuasion (Action), and decisions until confirmation. There is a positive (unidirectional) relationship between formal education, cosmopolitan, environmentally friendly paddy technology innovation, extension of environmentally friendly innovation, and agricultural technology information with increasing capacity of paddy farmers in Ciasmara village with a strong level of correlation (correlation), and there is influence in the use of biopesticides against pest reduction in lowland rice plants